Cross-scale causal information flow from the El Niño–Southern Oscillation to precipitation in eastern China - Y. Latif; K. Fan; K. Fan; G. Wang; M. Paluš (Earth System Dynamics)
The El Niño–Southern Oscillation (ENSO) is a dominant mode of climate variability influencing temperature and precipitation in distant parts of the world. Traditionally, the ENSO influence is assessed considering its amplitude. Focusing on its quasi-oscillatory dynamics comprising multiple timescales, we analyze the causal influence of phases of ENSO oscillatory components on scales of precipitation variability in eastern China, using information-theoretic generalization of Granger causality. We uncover the causal influence of the ENSO quasi-biennial component on the precipitation variability on and around the annual scale, while the amplitude of the precipitation quasi-biennial component is influenced by the low-frequency ENSO components with periods of around 6 years. This cross-scale causal information flow is important mainly in the Yellow River basin (YWRB), while in the Yangtze River basin (YZRB) the causal effect of the ENSO amplitude is dominant. The presented results suggest that, in different regions, different aspects of ENSO dynamics should be employed for prediction of precipitation.